2021
DOI: 10.1177/2046147x211014086
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the discussion on internal management of risk communication: A critique of the current risk communication literature

Abstract: The purpose of this paper is to build from the infrastructural approach to risk communication, rethink the internal management of risk communication, and critique the current literature’s discussion of how risks emerge, the role of the risk communication manager, and the decentralization of the risk communication function. Some of the risk communication literature is too general in terms of recognizing the nuance of the locus of risk, and the role(s) of stakeholders and communicators, which limit understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
3
0
1
Order By: Relevance
“…De acordo com o mesmo autor, a comunicação de risco tem surgido como um dos vetores mais importantes na ação governativa de diversos políticos à escala global, designadamente no âmbito da saúde, do ambiente, da regulação alimentar e do planeamento urbano. No entanto, esta parece ser uma perspetiva demasiado simplista, uma vez que apenas circunscreve o território do risco, mas ignora o papel dos stakeholders, dos comunicadores e da compreensão que pode ser gerada a partir da intervenção de múltiplos atores sociais (Lemon e VanDyke, 2021).…”
Section: Introductionunclassified
“…De acordo com o mesmo autor, a comunicação de risco tem surgido como um dos vetores mais importantes na ação governativa de diversos políticos à escala global, designadamente no âmbito da saúde, do ambiente, da regulação alimentar e do planeamento urbano. No entanto, esta parece ser uma perspetiva demasiado simplista, uma vez que apenas circunscreve o território do risco, mas ignora o papel dos stakeholders, dos comunicadores e da compreensão que pode ser gerada a partir da intervenção de múltiplos atores sociais (Lemon e VanDyke, 2021).…”
Section: Introductionunclassified
“…Scholarship has begun to investigate organizational capacities, structures, and processes for strategically communicating science to external publics, and potential consequences, and has called for more research investigating the same (Besley, 2020; Lemon and VanDyke, 2021; Rodder, 2020; Schwetje et al ., 2020; VanDyke and King, 2018; VanDyke and Lee, 2020; Vogler, 2020). For example, Koivumaki and Wilkinson (2020) found that during large-scale, funded research projects, which often require a public communication and/or engagement component, challenges often emerge in developing a common purpose and identity between researchers and communication professionals, which can impact the quality and cohesiveness of project-related science communication efforts.…”
Section: Introductionmentioning
confidence: 99%
“…Although existing risk-communication studies provide us with valuable insights into how isolated risk and emergency messages and individual government and municipal preparedness campaigns are received and interpreted by different groups of citizens (e.g. Frisby et al , 2013; Johansson et al , 2021), they do not inform us about the communication practitioners' own perceptions of such preventive and internal work (see also Lemon and VanDyke, 2021). With some exceptions (e.g.…”
Section: Introductionmentioning
confidence: 99%